البعد البيئي في مجال الصفقات العمومية - كبوية عبلة _ - دخوش لمياء (المسيلة, 2023)
بناءا على ما تم تناوله في هذا البحث "البعد البيئي في مجال الصفقات العمومية"، قام بإدماج البيئة في مجال الصفقات العمومية عن طريق تكريسها في المراحل التي المشرع الجزائري تمر بها الصفقة، وإلى توضيح العالقة بين الصفقات العمومية وحماية البيئة، ذلك أن قانون الصفقات العمومية في الجزائر تضمن فقط إشارات بسيطة لموضوع البعد البيئي في مجال الصفقات العمومية. Abstract : Based on what has been addressed in this research « the environmental dimension in the field of public markets », the Algerian legislator has included the environment in the field of public markets by devoting it in the stages that the contract goes through, and to clarify the relation between public agreements and environmental protection, because the law of public markets In Algeria only included simple references to the subject of the environmental dimension in the field of public markets.
Keywords: البعد البيئي - الصفقات العمومية